KEBIJAKAN HUKUM PIDANA TERHADAP MALPRAKTIK MEDIS PADA RUMAH SAKIT - Anny Retnowati; Elisabeth Sundari (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
Malpractice still occurs a lot, both by hospitals and doctors, although there are several legal instruments that regulate hospitals, as well as medical practice with sanctions for violators of health laws. The purpose of this study is to explore the deficiencies that exist in legal policies, and to propose new legal policies in order to optimally prevent and overcome hospital malpractice. The research method used is a normative research method by examining aspects of criminal law in health law concerning malpractice, as well as theories and expert opinions for better legal policy proposals. From the qualitative analysis of primary and secondary legal material data, the following results were obtained: first, there are weaknesses in the health law policy so that it cannot prevent and overcome malpractice optimally, namely incompleteness and lack of clarity regarding the formulation of malpractice and its strict sanctions, as well as a turn towards acts against the law and the limitations of the hospital's responsibility for malpractice committed by doctors or medical personnel. Second, a new legal policy that can be proposed, namely by clearly formulating and detailing the limits of hospital malpractice in health law, accompanied by strict sanctions or accountability both criminal, civil, and administrative, the hospital is also responsible for malpractice committed by doctors with conditions in certain conditions, procedural law must be lex specialis by, for example, imposing strict liability.